Energy metabolism in Arbidopsis thaliana: TCA cycle evolution, amino acids degradation and alternative pathways - Cavalcanti, João Henrique Frota (2015)
Plant mitochondrion are involved in several key cellular processes that goesbeyond energy production being also associated with programmed cell death, fruit ripening and even light- associate process including phorespiration and photosynthesis. In this context, mitochondria acquisition by host cell brought evolutionary advances for the existing plant cell by the preservation of diverse metabolic pathways including both those related to energy metabolism as well as those associated with lipids, nucleotides and vitamin biosynthesis. The most notorious heritage is related to the tricarboxylic acid (TCA) cycle. The TCA cycle is an essential pathway which is related to reducing power (NADH and FADH2) generation, nitrogen assimilation and photosynthesis optimization. It has been suggested that the TCA cycle operated as isolated steps prior endosymbiosis events and that only after mitochondria acquisition it was possible for it to be organized and function as a cycle. The TCA cycle is composed by a set of eight enzymes. However, each enzyme is encoded by several genes which are targeting not just to mitochondria, but that are also imported into others subcellular compartments. These TCA enzymes located in other subcellular compartiments result in likely a broader connection between mitochondria and other organelles (e.g. peroxissome and chloroplast) allowing a bypass of the intermediates of the cycle switching his operation to an unusual in non-cyclic modes flux. It is also currently accepted that under stress conditions, which leads to decreases in carbohydrate levels, the TCA cycle can function in non-cyclic flux mode due to diminishing of carbon skeleton the enter it making required that be fed by anauplerotic reactions. Therefore, amino acids become essential to support respiration and ATP synthesis under such situations. Compelling evidence have demonstrated that branched chain amino acids (BCAA) and lysine can supply electrons to the mitochondrial electron transport chain (mETC) by the action of the electron transfer flavoprotein (ETF)-ETF: ubiquinone oxidoreductase (ETF/ETFQO) system and associated dehydrogenases. In plants, only isovaleryl- CoA dehydrogenase (IVDH) and (D)-2-hydroxyglutarate dehydrogenase (D2HGDH) have been characterized as electron donnor to the ubiquinol pool via this system so far by the degradation of BCAA and lysine, respectively. In fact, BCAA catabolism is of pivotal importance to provide intermediates to TCA cycle, particularly under stress situations, whereas lysine shows a strict association with the TCA cycle being required to couple amino acid degradation and energy generation. The electron transfer through the mETC is tightly coupled to ATP synthesis and use electron donates by NADH and FADH 2 to phosphorylate ADP to ATP. However, our knowledged regarding the organization of the mitochondrial oxidative phosphorylation (OXPHOS) system and its alternatives pathways under energy limitation remains elusive. Thus, this thesis, which is focused on the function of respiration within the context of the role of the TCA cycle as well as the function of alternative electron donors to the mETC, iscomprised by three independent stand-alone chapters focusing on energy metabolism and alternative respiration in Arabidopsis thaliana. Hence to obtain a compreenhesive picture of how the TCA cycle evolved and to which extend its alternative pathways interact to adjust to different cellular and metabolic requirements, three experimental approaches were used: (i) by using bioinformatic approaches we investigated the evolutionary history of TCA cycle genes allowing the generation of a model for the origin of the TCA cycle genes in plants and connected its evolution with TCA cycle behavior under a range of stress; (ii) the importance of lysine deficiency were investigated by using an Arabidopsis mutant with reduced activity of the lysine biosynthesis enzyme L,L-diaminopimelate aminotransferase (dapat), and (iii) the metabolic reprograming associated with the OXPHOS system were investigated following carbon limitation.. In brief, the results presented here provided several novel findings and allowed, at least preliminarly, mechanistic interpretation thereof. First, it facilitate the elucidation of the evolutionary origem of the TCA cycle in land plants providing support to the contention that the origin of isoforms present in different subcellular compartments might be associated either with gene-transfer events which did not result in correct targeting or with new gene copys generated by genome duplication and horizontal transfer gene. Additionally, coexpression analyses of TCA cycle genes following different stress conditions in both shoot and root tissues demonstrated the presence of a large molecular plasticity and provided an explanation for the modular operation of the TCA cycle in land plants. Secondly, by using an Arabidopsis mutant with reduced activity of the Lys biosynthesis enzyme L,L-diaminopimelate aminotransferase (dapat) it was demonstrated that lysine biosynthesis deficiency mimics stress situation and impacts both plant growth and leaf metabolism.Thirdly, by evaluating OXPHOS system behavior following carbon starvation and how a range of amino acids can impact respiratory complexes it was possible to further demonstrate that OXPHOS is affected in function of the carbon source and that alternative pathways are induced under this condition.In addition, immunoblotting assays revealed that OXPHOS system is most likely regulated by posttranslational modification. When considered together these results highlight the complexity and specificity of plant respiration during evolution and that it is differently affected following energy limitation by the usage of alternative substrates. The results discussed here support the contention that ETF/ETFQO is an essential pathway able to donate electrons to the mETC and that amino acids are alternative substrates maintaining respiration under carbon starvation.The results obtained are discussed in the context of current models of metabolic evolution showing the strict association of energy metabolism with amino acids metabolism, and where possible, mechanistic insights are properly discussed. Key-words: alternative substrate respiration; energy deprivation; mitochondria evolution; mitochondria metabolism; neofunctionalization; OXPHOS; paralogous genes; stress response; TCA cycle;